Impact of an Immune Modulator Mycobacterium-w on Adaptive Natural Killer Cells and Protection Against COVID-19 - Jaiswal, Sarita Rani; Arunachalam, Jaganath; Saifullah, Ashraf; Lakhchaura, Rohit; Tailor, Dhanir; Mehta, Anupama; Bhagawati, Gitali; Aiyer, Hemamalini; Khamar, Bakulesh; Malhotra, Sanjay V.; Chakrabarti, Suparno (Frontiers in Immunology, 2022)
The kinetics of NKG2C+ adaptive natural killer (ANK) cells and NKG2A+inhibitory NK (iNK) cells with respect to the incidence of SARS-CoV-2 infection were studied for 6 months in a cohort of health-care workers following administration of heat killed Mycobacterium w (Mw group) in comparison to a control group. In both groups, COVID-19 correlated with a lower NKG2C+ANK cells at baseline. There was a significant upregulation of NKG2C expression and IFN-γ release in Mw group (p=0.0009), particularly in those with lower baseline NKG2C expression, along with downregulation of iNK cells (p<0.0001). This translated to a significant reduction in incidence and severity of COVID-19 in the Mw group (IRR-0.15, p=0.0004). RNA-seq analysis at 6 months showed an upregulation of ANK pathway genes and an enhanced ANK mediated ADCC signature. Thus, Mw was observed to have a salutary impact on the ANK cell profile and a long-term upregulation of ANK-ADCC pathways, which could have provided protection against COVID-19 in a non-immune high-risk population.